2019
DOI: 10.1253/circj.cj-18-1047
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Exercise Oscillatory Ventilation Loop and Prognosis of Heart Failure

Abstract: with left ventricular (LV) dysfunction exacerbates the V/Q mismatch, leading to progressively lower endtidal CO2 pressures (PETCO2). 7 Thus, EOV severity can be evaluated by detecting PETCO2 and V E, which indicate reduced pulmonary blood flow in patients with LV dysfunction, exacerbating the V/Q mismatch. During CPX, EOV appears as a loop (EOV loop) formed by graphing the 2 parameters, PETCO2 and V E. Hence, we hypothesized that the size of this loop during CPX would be larger in patients with severe cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In subjects with heart failure, Arena et al (2008) reported that patients with the largest ventilatory oscillation during the first half of exercise had significantly poorer prognoses and higher risk of cardiac events (Arena et al 2008). Nakade et al (2019) plotted and quantified the loop size of V  E versus end tidal partial pressure for CO 2 ; a larger loop was associated with cardiovascular death in heart failure patients (Nakade et al 2019). Quantification of EOV characteristics can provide useful information that may be neglected by a binary definition of EOV (Castro et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subjects with heart failure, Arena et al (2008) reported that patients with the largest ventilatory oscillation during the first half of exercise had significantly poorer prognoses and higher risk of cardiac events (Arena et al 2008). Nakade et al (2019) plotted and quantified the loop size of V  E versus end tidal partial pressure for CO 2 ; a larger loop was associated with cardiovascular death in heart failure patients (Nakade et al 2019). Quantification of EOV characteristics can provide useful information that may be neglected by a binary definition of EOV (Castro et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals may exhibit oscillatory breathing patterns that are abnormal but do not comply with any established criteria of EOV and are therefore neglected by a binary approach (Castro et al 2017). Furthermore, large ventilatory oscillations occurring at low exercise intensity (Arena et al 2008) and greater magnitude ventilatory oscillations (Nakade et al 2019) are associated with worse prognosis; this suggests that a method of quantifying the degree of EOV may provide additional prognostic information. EOV by current definitions may represent the abnormal extreme of a more insidious process characterized by a chronic deterioration of ventilatory control (Castro et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, according to severity, heart failure can be divided into acute heart failure and chronic heart failure. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Heart failure can be classified into left heart failure, right heart failure or whole heart failure depending on its location. In addition, according to severity, heart failure can be divided into acute heart failure and chronic heart failure 2…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we used CPX as an alternative modality for optimising pacing settings. CPX can be used to evaluate the severity of heart failure and the state of cardiac function during exercise by calculating the lowest minute ventilation and carbon dioxide output ratio7 and end-tidal carbon dioxide pressure,8 respectively. Therefore, CPX represents an effective alternative to TTE in patients with AF that offers an added advantage of exercise tolerance assessment.…”
Section: Discussionmentioning
confidence: 99%